2009
DOI: 10.1108/13581980910934045
|View full text |Cite
|
Sign up to set email alerts
|

Market risk disclosure: evidence from Malaysian listed firms

Abstract: PurposeThe purpose of this paper is to investigate the market risk disclosure practices among Malaysian listed firms. Specifically, it aims to examine the level of compliance with FRS132: Financial Instruments – Disclosure and Presentation for financial periods beginning or after 2006.Design/methodology/approachThe approach taken is content analysis and coding procedure.FindingsAlthough a large number of companies have shown compliance with FRS132 in relation to disclosing the financial risk management policy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
(23 reference statements)
1
27
2
3
Order By: Relevance
“…We included in our investigation the financial -year end notional amount of foreign currency derivatives (in Ringgit Malaysian) such as the Forward and Future contracts, whereas, for interest rate derivates, Forward and Swaps contracts. Othman and Ameer (2009) report that Forward contracts are used in high proportion to hedge market risks by Malaysian companies followed by Future and Swap contracts. Out of 427 firms, only 112 firms met our criteria of non-missing data on derivatives and other variables and therefore sufficient firm-year observations over the period, 2003 -2007.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…We included in our investigation the financial -year end notional amount of foreign currency derivatives (in Ringgit Malaysian) such as the Forward and Future contracts, whereas, for interest rate derivates, Forward and Swaps contracts. Othman and Ameer (2009) report that Forward contracts are used in high proportion to hedge market risks by Malaysian companies followed by Future and Swap contracts. Out of 427 firms, only 112 firms met our criteria of non-missing data on derivatives and other variables and therefore sufficient firm-year observations over the period, 2003 -2007.…”
Section: Samplementioning
confidence: 99%
“…Malaysian firm seem to prefer the customization and flexibility of Forward foreign exchange contracts over other standardized foreign exchange Options and Future contracts. The rest of the firms have used in different proportion the Forward and Swaps contracts for foreign exchange and interest rate risk management respectively (Othman and Ameer, 2009). It is important to point out here that all the sample firms except banks disclosed that trading in derivatives is not allowed under their financial risk management policy.…”
Section: Samplementioning
confidence: 99%
“…Unlike many prior studies, FID was examined either by using the prior standards such as MASB 24 (Hassan & Salleh 2010) and FRS 132 (Othman & Ameer 2009;Zadeh & Eskandari 2012), or by focusing on voluntary disclosure (Bamber & McMeeking 2010;Ismail & Rahman, 2011). This study extends prior research by focusing on MFRS 7, the current globally-accepted accounting standard.…”
Section: Introductionmentioning
confidence: 99%
“…Amran et al (2009) have shown significant positive relationship between entity's size and extent of risk management disclosure. Other authors (Othman, Ameer, 2009;Puccia, Tutinob and Marulli, 2012) analysed the compliance of de facto disclosures with national and international regulatory requirements. Significant variations have been found.…”
Section: Introductionmentioning
confidence: 99%